Disentangling the Effects of Spinal Cord Injury and Related Neuropathic Pain on Supraspinal Neuroplasticity: A Systematic Review on Neuroimaging - Huynh, Vincent; Rosner, Jan; Curt, Armin; Kollias, Spyros; Hubli, Michèle; Michels, Lars (Frontiers in Neurology, 2020)
Spinal cord injury (SCI) and its accompanying changes of brain structure and function have been widely studied and reviewed. Debilitating chronic neuropathic pain (NP) is reported in 53% of SCI patients and brain changes have been shown to be involved with the presence of this secondary complication. However, there is yet a synthesis of current studies that investigated brain structure, resting connectivity and metabolite changes that accompanies this condition. In this review, a systematic search was performed using MeSH heading search terms in PubMed and SCOPUS to gather the appropriate published studies. Neuroimaging studies that investigated supraspinal structural, resting-state connectivity and metabolite changes in SCI subjects with NP were included. To this end, voxel-based morphometry (VBM), diffusion tensor imaging (DTI), resting-state functional MRI (rsfMRI), magnetic resonance spectroscopy (MRS) and positron-emission tomography (PET) studies were summarised and reviewed. Further inclusion and exclusion criteria allowed delineation of appropriate studies that included SCI subgroups with and without NP. A total of 12 studies were eligible for qualitative synthesis. Overall, current studies that investigated NP associated changes within the SCI cohort show primarily metabolite concentration alterations in sensory-pain processing regions, alongside bidirectional changes of brain structure. Moreover, in comparison to healthy controls, there remains limited evidence of structural and connectivity changes but a range of alterations in metabolite concentrations in SCI subjects with NP. There is some evidence suggesting that the magnitude and presence of NP following SCI results in both adaptive and maladaptive structural plasticity of sensorimotor regions, alongside altered metabolism of brain areas involved with descending pain modulation, pain perception (i.e., anterior cingulate cortex) and sensory integration (i.e., thalamus). However, based on the fact that only a few studies investigated structural and glucose metabolic changes in chronic SCI subjects with NP the underlying mechanisms that accompany this condition remains to be further elucidated. Future cross-sectional or longitudinal studies that aim to disentangle NP related to SCI may benefit from stricter constraints in subject cohorts, controlled sub-groups, improved pain phenotyping and implementation of multi-modal approaches in order to discover sensitive biomarkers that profile pain and optimise treatment in SCI subjects with NP.